The impact of agricultural policy on income diversity among farmers in the European Union in 2005–2017 - Smędzik-Ambroży, Katarzyna; Sapa, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The aim of paper is to answer to the question whether the EU’s Common Agricultural Policy reduces the differences in the average agricultural income between the EU-15 countries and those that joined the EU in 2004. The hypothesis was assumed that the CAP subsidies reduce the differences in agricultural income between these two groups of countries. Spreads between average income of farmers from the old and new members were calculated. The analysis is carried out in two variants. In the first one, the agricultural income does not include the CAP support, in the second one the agricultural income covers all CAP subsidies. The spatial scope of research involves two groups of countries: EU-15 (Belgium, the Netherlands, Luxembourg, France, Germany, Italy, the United Kingdom, Denmark, Ireland, Greece, Spain, Portugal, Finland, Austria and Sweden) and EU-8 (the Czech Republic, Poland, Slovakia, Lithuania, Latvia, Estonia, Hungary and Slovenia). The subjective scope of the survey covers representative farms from the EU countries (representing 4,045,300–5,295,930 farms in the EU countries, depending on the investigated year). The time frame of the analyses concerns the years 2005–2017. The data from the Farm Accountancy Data Network (FADN) are used. The study positively verifies the hypothesis that: subsidies from the CAP cause a decrease in the differences in average agricultural income between the EU-15 and the EU-8 countries. This contributes to an increase in economic sustainability and in the territorial cohesion of agriculture for the EU countries.

Celem artykułu była odpowiedź na pytanie, czy polityka rolna UE powoduje zmniejszanie różnic w wartości dochodów rolniczych pomiędzy krajami UE-15 i krajami, które przystąpiły do UE w 2004 roku (UE-8). W artykule postawiono hipotezę, że subwencje ze wspólnej polityki rolnej (WPR) powodują zmniejszanie różnic w dochodach rolniczych pomiędzy tymi grupami krajów. Obliczono rozpiętości pomiędzy średnimi dochodami rolników z krajów UE-15 i UE-8 (tj. bez Malty i Cypru). Analizę zrealizowano w dwóch wariantach. W pierwszym, dochód rolników nie obejmował wsparcia WPR, w drugim wariancie, dochody rolników uwzględniały różne subwencje WPR. Zakres przestrzenny analiz obejmował kraje UE-15 (tzw. stare kraje), czyli: Belgię, Niderlandy, Luksemburg, Francję, Niemcy, Włochy, Wielką Brytanię, Danię, Irlandię, Grecję, Hiszpanię, Portugalię, Finlandię, Austrię i Szwecję oraz kraje UE-8 (tzw. nowe kraje), czyli: Czechy, Estonię, Litwę, Łotwę, Polskę, Słowację, Słowenię i Węgry. Zakres podmiotowy obejmował reprezentatywne gospodarstwa rolne z tych krajów (reprezentowały one w zależności od roku od 4 045 300 gospodarstw do 5 295 930 gospodarstw rolnych w krajach UE). Analizy obejmowały lata 2005–2017. Dane pochodziły z europejskiego FADN (Farm Accountancy Data Network). W wyniku analiz pozytywnie zweryfikowano hipotezę, że subwencje z WPR powodują zmniejszanie różnic w dochodach rolniczych pomiędzy UE-15 i grupą krajów, które przystąpiły do UE w 2004 roku. Przyczynia się to do zwiększenia zrównoważenia ekonomicznego oraz powoduje zwiększenie spójności terytorialnej rolnictwa z krajów UE.
Keywords: agricultural income; income disparities; the European Union; the Common Agricultural Policy; dochody rolnicze; nierówności dochodowe; Unia Europejska; wspólna polityka rolna